The PENGARUH TERAPI AKUPRESUR TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POST PARTUM DI PKU MUHAMADIYAH BANTUL - Liliana, Anita; Wahyuningsih, Melania (Coping: Community of Publishing in Nursing; Vol 8 No 4 (2020): Desember 2020DO - 10.24843/coping.2020.v08.i04.p10, 2020)
Abstract Adequacy of milk production in the newborns will affect the success of exclusive breastfeeding. Not all postpartum mothers are able to increase milk production in the postpartum period. Acupressure at the meridian points is one way to increase milk production in postpartum mothers. This study aims to determine the effect of acupressure therapy on increasing breast milk production in postpartum mothers at PKU Muhamadiyah Bantul. This study was a quantitative study  a quasi-experimental research design with pre-test and post-test nonequivalent control group. The number of respondents in each group was 17 people. The treatment given was acupressure at the meridian points for 5 minutes on days 2 and 3of poatpartum. Breastfeeding adequacy was assessed before treatment and on day 4 postpartum. Data were analyzed by Mc Nemar analysis. The results showed that there was a significant difference in breast milk production before and after acupressure with p value of 0.000 (p value <0.05). There was a significant difference in breast milk production in the control group before and after being given the breastfeeding technique leaflet p value 0.001 (p value <0.05). Conclusion: There is no significant difference in breast milk production after being given acupressure and after being given leaflets about breastfeeding techniques at PKU Muhamadiyah Bantul p value 0.100 (p value> 0.05).  Keywords: acupressure, breast milk production, postpartum